2005
DOI: 10.4049/jimmunol.175.10.6764
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Thrombin-Activatable Fibrinolysis Inhibitor Protects against Sepsis-Induced Liver Injury in Mice

Abstract: Thrombin-activatable fibrinolysis inhibitor (TAFI), also known as carboxypeptidase R, has been implicated as an important negative regulator of the fibrinolytic system. In addition, TAFI is able to inactivate inflammatory peptides such as complement factors C3a and C5a. To determine the role of TAFI in the hemostatic and innate immune response to abdominal sepsis, TAFI gene-deficient (TAFI−/−) and normal wild-type mice received an i.p. injection with Escherichia coli. Liver TAFI mRNA and TAFI protein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 60 publications
2
65
1
1
Order By: Relevance
“…30 In a recently published Escherichia coli-induced peritonitis model in proCPB Ϫ/Ϫ mice, there was no evidence of perturbed fibrinolysis, as measured by D-dimer levels in plasma or the extents of fibrin deposition in lung and liver tissues. 31 Thus, the role of CPB as a fibrinolysis inhibitor in mice does not appear to be as significant as that in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 In a recently published Escherichia coli-induced peritonitis model in proCPB Ϫ/Ϫ mice, there was no evidence of perturbed fibrinolysis, as measured by D-dimer levels in plasma or the extents of fibrin deposition in lung and liver tissues. 31 Thus, the role of CPB as a fibrinolysis inhibitor in mice does not appear to be as significant as that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…31 Studies have shown that C3a and C5a are capable of priming hepatocytes for regeneration, which is mediated by C3a and C5a binding to the C3aR and C5aR on Kupfer cells, a role distinct from the usual inflammatory role ascribed to C3a and C5a. 33,34 The result is consistent with the interpretation that there is more local C5a generation in the liver in the proCPB Ϫ/Ϫ mice in the peritonitis model, thus leading to enhanced liver regeneration and reduced liver necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritonitis was induced as described previously (9,23,24). In brief, E. coli O18:K1 was cultured in Luria-Bertani medium (Difco) at 37°C, harvested at mid-log phase, and washed twice before inoculation.…”
Section: Induction Of Peritonitismentioning
confidence: 99%
“…To score liver injury, interstitial inflammation, thrombi, hepatocellular necrosis and portal inflammation were analyzed. Lungs were scored for interstitial inflammation, edema, pleuritis and thrombi [22].…”
Section: Organ Pathologymentioning
confidence: 99%